A case of end‐to‐end anastomotic repair for the proximal main pancreatic duct injury in a child. Issue 3 (August 2016) - Aoi, Shigeyoshi; Kimura, Kouseki; Tsuda, Tomoki; Takahashi, Shigeru
Abstract : The therapeutic strategies for the proximal transection of pancreas in children, consequently accompanying main pancreatic duct (MPD) damages, remain controversial for its rare incidence. We experienced one case of proximal MPD injury in a child and performed end‐to‐end anastomotic repair easily without major postoperative complications using intraoperative ultrasonography. Such patients could be discharged from hospital after a short period; however, the long‐term result must be clarified.